2021
DOI: 10.3389/fnmol.2021.705023
|View full text |Cite
|
Sign up to set email alerts
|

Kampo Formulae for the Treatment of Neuropathic Pain ∼ Especially the Mechanism of Action of Yokukansan ∼

Abstract: Kampo medicine has been practiced as traditional medicine (TM) in Japan. Kampo medicine uses Kampo formulae that are composed of multiple crude drugs to make Kampo formulae. In Japan, Kampo formulae are commonly used instead of or combined with Western medicines. If drug therapy that follows the guidelines for neuropathic pain does not work or cannot be taken due to side effects, various Kampo formulae are considered as the next line of treatment. Since Kampo formulae are composed of two or more kinds of natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 133 publications
0
10
0
Order By: Relevance
“…In clinical practice, traditional Japanese medicines (called Kampo medicines) composed of crude chemicals isolated from plants are prescribed for various purposes such as analgesia along with Western medicines in Japan [320][321][322][323][324][325]. Daikenchuto is one of most frequently prescribed Kampo medicines and is used to treat cold sensation and dysmotility in the abdomen.…”
Section: Actions Of Plant-derived Compounds On Nerve Ap Conductionmentioning
confidence: 99%
“…In clinical practice, traditional Japanese medicines (called Kampo medicines) composed of crude chemicals isolated from plants are prescribed for various purposes such as analgesia along with Western medicines in Japan [320][321][322][323][324][325]. Daikenchuto is one of most frequently prescribed Kampo medicines and is used to treat cold sensation and dysmotility in the abdomen.…”
Section: Actions Of Plant-derived Compounds On Nerve Ap Conductionmentioning
confidence: 99%
“…A recent clinical study on acute postoperative pain after breast cancer surgery also demonstrated the perioperative anxiolytic effects of YKS [ 12 ]. Furthermore, although reviews have described the mechanism of action of YKS in neuropathic and chronic pain [ 13 ], no reports on its action on acute postoperative pain have been presented. However, since YKS has 5-HT 1A receptor agonist activity, we speculated that YKS would also exert an analgesic effect on acute pain, such as postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…Kampo medicine, used in traditional Japanese medicine, has been used to treat a variety of pains, with or without Western medicine ( Arai et al, 2020 ; Sunagawa et al, 2021 ). Yokukansan (YKS; Yi-Gan San in Chinese), which was firstly described in the Bao-ying jin-jing-lu written in 1,550, is a traditional Kampo medicine consisting of seven herbs.…”
Section: Introductionmentioning
confidence: 99%